#EntreViagenseAprendizagens: study protocol of a school-based intervention to promote well-being and healthy lifestyles among adolescents - Francisco, Rita; Raposo, Beatriz; Hormigo, Mafalda; Sesifredo, Mónica; Carvalho, Ana; Justo, Ana; Godinho, Cristina Albuquerque (Frontiers in Psychology, 2023)
Background Adolescence is a critical period of development in which well-being usually decreases, mental health problems (e.g., depression, anxiety) increase, and lifestyles become less healthy. Schools are a primary setting for the promotion of the well-being and overall health of adolescents, and preventive actions should be a priority within the scope of health-promoting schools. #EntreViagenseAprendizagens is a school-based intervention aiming to promote well-being and healthy lifestyles among adolescents based on social and emotional learning, positive psychology, and health education approaches. Methods This protocol describes a school-based intervention, #EntreViagenseAprendizagens, that will be implemented in several schools in Portugal. The program is aimed at 8th and 9th grade students (14–16 years old) and comprises 20 weekly sessions. One of the sessions is aimed at the students’ parents/guardians. The intervention content targets social and emotional skills, health literacy (physical and mental health), healthy lifestyles, character strengths, and well-being. An experimental design will be used in the intervention evaluation. Eighth grade classes will be randomly assigned to the intervention group or the control group. All students complete the same assessment protocol at baseline, post-intervention, and 9-month follow-up. The impact assessment protocol includes measures related to well-being, health literacy, health-related knowledge, attitudes and behaviors, relationships with others, social and emotional skills, and sociodemographic data. Process evaluation includes evaluation forms at the end of each session and at the end of the program and focus groups with students, parents, and teachers at the end of the program. Discussion This school-based intervention may play an important role in promoting students’ well-being and in preventing unhealthy lifestyles and socio-emotional maladjustment, by focusing on the development of social and emotional skills and health literacy among adolescents, empowering them to face the changing future and grow up healthy. Furthermore, this project aims to provide relevant scientific findings that can contribute to the development of better health-promoting schools.